Financial Toxicity Encountered in Therapeutic Radiopharmaceutical Clinical Development for Ovarian Cancer - Charles A. Kunos; Rita Abdallah (MDPI AG, 2020)
Financial toxicity or the debt a cancer survivor incurs from the costs of their medical cancer care is an understudied aspect in the clinical development of experimental therapeutic agents. The United States National Cancer Institute (NCI) Cancer Therapy Evaluation Program studies experimental therapeutic agents like radiopharmaceuticals in both early and late phase trials, which provide opportunities to comprehend more clearly the possible sources of financial toxicity incurred by cancer survivors. We reviewed the academic scholarship describing fiscal and social costs involved in the development of therapeutic radiopharmaceuticals. Because many ovarian cancer survivors outlive their disease through initial and, perhaps, multiple treatment courses, these women and their treatments provide context for our discussion on financial toxicity. 16 (27%) of 60 articles discuss financial toxicity incurred by women with ovarian cancer; none described financial toxicity associated with regulatory agency-approved or experimental therapeutic radiopharmaceuticals. Fiscal costs of radiopharmaceutical dose and schedule and social costs of individual productivity loss or asset expenditure arose as primary financial toxicities. The development of radiopharmaceuticals for women with ovarian cancer remains a high priority for the NCI Cancer Therapy Evaluation Program. Weighing radiopharmaceutical clinical benefit against measures of financial toxicity is challenging and warrants further study in prospective radiopharmaceutical clinical trials.